PENGEMBANGAN MEDIA INTERAKTIF DALAM PENGENALAN KATA BERMAKNA PADA ANAK - Nuri Cahyati; Syafdaningsih Syafdaningsih; Rukiyah Rukiyah (UPI Kampus Cibiru, 2018)
Abstract:. The purpose of this study is to produce a interactive media in meaningful word recognition. The development of interactive media in meaningful word recognition using a combination of ADDIE development model and Tessmer evaluation. The ADDIE development model consists of five stages, namely the analysis, design, development, implementation and evaluation phase. At the evaluation stage, the formative evaluation proposed by Tessmer consists of stages, namely self evaluation stage, expert review, one-to-one evaluation, small group evaluation. grade collection techniques used interviews, vadidation sheets, and observations. Experimental results obtained the average score of the results of the assessment of interactive media in meaningful word recognition experts obtained 3.56% results and material experts of 3.81% to obtain an average of 3.68% (very valid category). The one to one evaluation stage was conducted by three students who used picture book of animals with a favorite theme obtained average 75% (practical) children observation result. The small group evaluaion stage was carried out by nine students who used the favorite animal-themed picture books obtained by an average 79.16% (practical) children's observation result, the field test stage was not performed because it only tested the validity and practicability level, not the potential effects of the use illustrated Interactive media products. Of all the stages that have been done then it can be concluded that the interactive media in meaningful word recognition declared valid and practical for the child. Keyword: Development Interactive media, meaningful word recognition, 5-6 years old . Abstrak: Penelitian ini bertujuan untuk mengembangkan media interaktif dalam pengenalan kata bermakna. Pengembangan media interaktif dalam pengenalan kata bermaknaini menggunakan kombinasi model pengembangan ADDIE dan evaluasi Tessmer. Model pengembangan ADDIE terdiri dari lima tahap, yaitu tahap analisis, perancangan, pengembangan, implementasi, dan tahap evaluasi. Pada tahap evaluasi dilakukan evaluasi formatif yang dikemukakan oleh Tessmer terdiri dari tahap, yaitu tahap self evaluation, expert review, one-to-one evaluation, small group evaluation. Teknik pengumpulan data menggunakan wawancara, lembar validasi, dan observasi. Hasil expert review diperoleh nilai rata-rata hasil penilaian dari media interaktif dalam pengenalan kata bermakna oleh ahli media didapatkan hasil 3,56 % dan ahli materi sebesar 3.81% sehingga diperoleh rata-rata sebesar 3,68 % (kategori sangat valid). Tahap one to one evaluation dilakukan oleh tiga orang siswa yang menggunakan media interaktif dalam pengenalan kata bermakna didapatkan rata-rata hasil observasi anak 75% (praktis). Tahap small group evaluaion dilakukan oleh sembilan orang siswa yang menggunakan media interaktif dalam pengenalan kata bermakna didapatkan rata-rata hasil observasi anak 79.16% (praktis), tahap field test tidak dilaksanakan dikarenakan hanya menguji tingkat kevalidan dan kepraktisan, tidak sampai pada efek potensial dari penggunaan produk media interaktif. Dari semua tahap yang telah dilakukan maka dapat disimpulkan bahwa media interaktif dalam pengenalan kata bermakna dinyatakan valid dan praktis bagi anakKata Kunci: Pengembangan Media Interaktif, pengenalan kata bermakna, usia 5-6 tahun